Analisis Dan Pengembangan Sistem Informasi Penjualan Kambing Aqiqah Berbasis Web Dengan Metode Pieces Dan Waterfall - Rizal Ardiansyah; Ali Ikhwan (STIKOM Tunas Bangsa Pematangsiantar, 2026)
The rapid development of information technology today is in line with the increasing use of the internet, both in Indonesia and around the world. One of the significant impacts of this growth is the emergence of changes in business models, particularly the rise of digital sales applications. Sales applications can be defined as marketing activities for goods or services through the internet, utilizing modern web-based marketing techniques. With the adoption of digital marketing concepts, business actors such as livestock farmers can market their livestock more quickly and efficiently. In this study, the technology applied is the development of a web-based livestock sales application. Currently, the issue found in the field is that the process of selling livestock for Aqiqah purposes is still carried out manually. Farmers must offer their products directly to potential buyers without any integrated information media. This condition causes various obstacles and limitations in the marketing process. Therefore, the utilization of technology becomes an appropriate solution to address these problems. The proposed and applied solution in this research is the development of a web- based information system for the sale of livestock for Aqiqah. This application is expected to help farmers expand their marketing reach and assist consumers in obtaining information and making purchases more practically and efficiently.